(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Morphological and immunohistochemical studies of complicated lipofilling outcomes revealed five main types of tissue reactions: lipogranuloma, cyst with fibrous capsule, fibroma, lipoma, and non-encapsulated fat necrosis. Each form had a different anatomical location, time of manifestation, and nature of the inflammatory-reparative response.